Penerapan Peraturan Dewan Pers terhadap Pemberitaan Bunuh Diri di Kampar Riau - Noprio Sandi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to determine which points of Press Council Regulation Number: 2/PERATURAN-DP/III/2019 concerning Guidelines for Reporting on Acts and Attempted Suicide have been violated by a number of cyber media and to determine whether the families of suicide victims are aware of the number of suicide reports published that violate or not. Also to provide knowledge to suicide observers so they can prevent suicide in other children. The method used is qualitative research with a combined approach and uses a case study model, content analysis methods and interviews. The results of the study, 14 of the 20 points of Press Council Regulation Number: 2/PERATURAN-DP/III/2019 concerning Guidelines for Reporting on Acts and Attempted Suicide were violated by 14 cyber media (these 14 points are the most frequently violated). These violations are not known to the victims' families. Therefore, the implications of this research can provide education for the victims' families, after knowing the violations, the victims' families can prepare the next strategic steps to seek justice for the mistakes made by a number of cyber media. Meanwhile, observers, particularly those concerned with suicide in Riau, can also prepare further steps to prevent others, especially teenagers and children, from imitating these acts and attempts. This strategic step is expected to have a deterrent effect on cyber media outlets that violate regulations, and encourage them to be more cautious in reporting on suicide acts and attempts in the future.